Can prisons work? : the prisoner as object and subject in modern corrections - Duguid, Stephen (University of Toronto Press, 2000)
Can individuals be reformed or rehabilitated in the prison? A persistent body of work indicates that rehabilitation and/or reformation through incarceration is illusory. Exceptions, according to this view, are the result of accident, not design. For many practitioners in corrections systems, the incarceration of criminals is a "fact" and the task of prisons is to isolate, deter, and punish and only then, perhaps reform the criminal. In "Can Prison Work?" Stephen Duguid contends that both critics and defenders of incarceration have erred in making the prisoner the object rather than the subject of their discourse; the critics see prisoners as victims of a monstrous institution and the defenders view them as incorrigibles persuaded only by coercion or manipulation. Duguid begins by reviewing the philosophical and cultural contexts that led to the idea of "curing" criminals (in addition to deterring crime) through treatment and incarceration, presenting diverse historical commentaries from Plato and Socrates to former inmates. The two dominant approaches to modern corrections are also discussed, the one based on sociology and the one based on psychology - the latter being seen as responsible for the rise in the twentieth century of a medicalized approach to corrections. It was the collapse of this 'medical' model (in the 1970s) that created possibilities for innovative approaches in penology and four of these approaches are examined in some depth. Focusing on prisons with broadly conceived educational programs organized by people from outside the field of corrections, Duguid describes how programs in Canada, England, Scotland, and the United States were successful largely because the relationship with prisoner-students was built around notions of reciprocity, mutual respect, and individual development. Empirical data from an extensive follow-up study of the Canadian program is presented as evidence of the potential success using these kinds of approaches. In each of these cases, however, these programs, others like them, were eventually terminiated by prison authorities. The book concludes with the exploration of the tension between prison systems and outsiders engaged with programs within prisons. It argues against the re-emergence of a new medical model in favour of more humane - and human - approaches to individual change and reformation. Winner of the Harold Adams Innis Prize, awarded by the Canadian Federation for the Humanities and Social Sciences